PENGARUH SERVANT LEADERSHIP DAN MOTIVASI TERHADAP KINERJA ANGGOTA SUBDIT REGIDENT DITLANTAS POLDA JATIM - jurnalmap map; Hendik Arianto; Indra Prasetyo; Mei Indrawati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
A success of an organization is the role of the human resources involved. Therefore, it takes a qualified individual quality to manage the organization. The things related to human resources are leadership, leadership is often equated with a comfort, a pleasant position and always desired by many people. However, in the reform era as it is today, the perspective of leadership has shifted where most of the leaders just ordered, demanded to be served, and lacked care for subordinates or what happened in the field, the process of devolution of power too much favored. The type and approach of this proposed research is causality research, which is a study focused on proving the influence of servant leadership and motivation as independent variables on the performance of members of the Regencies Sub-Directorate of Ditlantas of East Java Regional Police as dependent variables. The design of this study is to research carried out by using a questionnaire instrument. From the description of the results of the discussion of research Influence of Servant Leadership and Motivation Performance Against Members Subdit Regident which has been discussed above, researchers can draw the conclusion that the form of servant leadership (Servant Leadership) and be able to motivate much needed in the middle of the environment at work at the moment to improve performance member.Keywords: servant leadership, motivation, performance